Improved biopharmaceutical properties of carvedilol employing α-tocopheryl polyethylene glycol 1000 succinate-based self-emulsifying drug delivery system. (2nd November 2018) - Halder, Shimul; Ogino, Mizuki; Seto, Yoshiki; Sato, Hideyuki; Onoue, Satomi
Abstract: The main objective of this study was to develop a self-emulsifying drug delivery system (SEDDS) of carvedilol (CAR) with improved oral absorption and hepatoprotective properties. SEDDS-CAR was prepared based on d -α-tocopheryl polyethylene glycol 1000 succinate (TPGS) and physicochemically characterized. Pharmacokinetic behaviors after the oral administration of CAR samples in rats were evaluated to clarify the possible enhancement of the oral absorption of CAR. The hepatoprotective effects of orally dosed CAR samples were assessed in a rat model of acute hepatic injury induced by carbon tetrachloride (CCl4 ). SEDDS-CAR showed the immediate formation of fine micelles with a mean droplet size of 84 nm when introduced in aqueous media. SEDDS-CAR improved the dissolution behavior of CAR in distilled water as evidenced by at least five-fold higher solubility than the equilibrium solubility of CAR. After the single oral administration of SEDDS-CAR (10 mg-CAR/kg) in rats, enhanced CAR exposure was observed with an increase of AUC0–∞ showing a 2.5-fold increase compared with crystalline CAR. In CCl4 -treated rats, orally dosed SEDDS-CAR (10 mg-CAR/kg, p.o .) led to 91.8 and 91.2% reductions of ALT and AST, respectively; however, crystalline CAR was found to be less effective. From these findings, SEDDS-CAR might be an efficacious oral dosage option for enhancing the hepatoprotective potential of CAR.